The Prevalence and The Relationship of Workplace Bullying and Nurses Turnover Intentions: A Cross Sectional Study - Essa H. Al Muharraq MSN, RN; Omar G. Baker PhD, RN; Sultan M. Alallah MSN, RN (SAGE Publishing, 2022)
Introduction: Sustaining a healthy work environment is a major challenge for health care organizations worldwide. Nursing professionals are often exposed to workplace bullying, which imposes serious challenges to nursing retention. Objectives: To determine the prevalence of workplace bullying and turnover intention among nurses, and to investigate the relationship between workplace bullying and nurse turnover. Methods: A cross-sectional correlational design. Convenience sampling was applied, whereby 347 nurses working in a tertiary medical city in Riyadh, Saudi Arabia, were recruited. Data were collected using the Negative Acts Questionnaire and the Anticipated Turnover Scale. Results: The rate of workplace bullying was high, bullying occurred at a cumulative rate of 33.4% ( n  = 116). Work related bullying behaviors formed the most common bullying acts with (34.5%) followed by personal bullying with (31.1%) meanwhile physical intimidating accounted by (25.6%). Among the participants, 31.7% exhibited a high turnover intention. The demographic variable age was revealing an inverse correlation with workplace bullying. There was a positive significant correlation between workplace bullying and turnover intentions ( r  = .24, p  < 0.01). Conclusion: The alarming prevalence of both bullying and turnover intention among participants confirms that when nurses are exposed to workplace bullying, they are more likely to demonstrate an increased intention for turnover. Managers are urged to use proper enforcement of anti-bullying policies along with education and training to create a healthy environment and mitigate workplace bullying.